1996
DOI: 10.1097/00005392-199609000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation into the Long-term Defunctionalized Bladder

Abstract: Renal transplantation into a long-term defunctionalized bladder can be performed safely in carefully selected patients. Bladder function and continence should be confirmed before transplantation using a program of progressive bladder rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In adults, a contracted bladder, if due primarily to prolonged defunctionalization, should also improve with restoration of the urinary flow [2]. Serrano et al [2]reported that bladders can be successfully restored after 26 years of defunctionalization.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In adults, a contracted bladder, if due primarily to prolonged defunctionalization, should also improve with restoration of the urinary flow [2]. Serrano et al [2]reported that bladders can be successfully restored after 26 years of defunctionalization.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, a contracted bladder, if due primarily to prolonged defunctionalization, should also improve with restoration of the urinary flow [2]. Serrano et al [2]reported that bladders can be successfully restored after 26 years of defunctionalization. However, there may be instances in which chronic inflammation or previous surgery may cause extreme fibrosis leading to impaired bladder recovery, including chronic tuberculosis or schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations